Intraoperative "Kounis syndrome" that improved electrocardiography changes and hemodynamic situation afteradministering nitroglycerine - Sánchez,Victoria O. (2014)
A 58-year-old female without cardiovascular risk factors, was going to be operated to repair the rotator cuff. Induction and interscalene brachial plexus block were uneventful, but after her placement for surgery the patient started with severe bronchospasm, hypotension, cutaneous allergic reaction and ST elevation on the electrocardiogram. An anaphylactic shock was suspected and treated but until the perfusion of nitroglycerina was started no electrocardiographic changes resolved. After necessary diagnostic test the final diagnosis was variant I of Kounis syndrome due to cefazolin and rocuronium. Ephinephrine is the cornerstone of treatment for anaphylaxis but should we use it if the anaphylactic reaction is also accompanied by myocardial ischemia? The answer is that we should not use it because myocardial ischemia in this syndrome is caused by vasospasm, so it would be more useful drugs such as nitroglycerin. But what if we do not know if it is a Kounis syndrome or not? In this article we report our experience that maybe could help you in a similar situation.